Developing Community-Based Tourism Potential In The Tanjung Anom Reservoir Tourism Village, Central Lampung Regency - Sudarman Mersa (Dealings Foundation Institute, 2025)
Community-based tourism (CBT) development is a strategic approach to improving community welfare, particularly in rural areas rich in natural and cultural resources. Embung Tanjung Anom, located in Central Lampung Regency, is one such local destination that has been developed through active community participation under the CBT concept. However, the implementation of CBT still faces various challenges, such as inadequate infrastructure, limited human resource capacity, and weak promotional and institutional management. This study aims to analyze the application of CBT principles, identify supporting and inhibiting factors, and formulate strategic models for developing community-based tourism potential in Embung Tanjung Anom. A qualitative descriptive approach was employed, using data collection techniques including interviews, observations, and documentation, with SWOT analysis as the analytical tool. The findings indicate that the Tourism Awareness Group (Pokdarwis), largely comprised of local youth, plays a central role in organizing attractions and promoting the site. However, tourism development remains suboptimal due to unequal distribution of economic benefits, lack of tourism education and training, and poor road access. Development strategies are directed towards strengthening tourism education, enhancing digital promotion through collaboration with tourism influencers, and positioning Embung Tanjung Anom as a leading tourism destination in the region. This study proposes a strategic model for community-based tourism development that emphasizes synergy among communities, government, and the private sector to achieve sustainable tourism outcomes. Keywords: Community-Based Tourism, Embung Tanjung Anom, Pokdarwis, development strategy, sustainable tourism.